How can climate adaptation policy enhance urban climate resilience? Empirical evidence from China - Ana Yin; Ziqi Liu (PLoS ONE, 2025)
As the primary carriers of population aggregation, cities face severe climate risks and challenges. This paper examines whether and how climate adaptation policy can enhance urban climate resilience. Based on panel data from 57 cities in China’s typical ecologically fragile region—the Yellow River Basin—from 2010 to 2022, this study employs the Synthetic DID method to evaluate China’s Climate Adaptive City Construction Pilot Program (CACCP). The results indicate that the CACCP policy can significantly enhance urban climate resilience, and this conclusion remains valid after a series of robustness tests. The CACCP policy mechanism reveals that green bond instruments play an effective mediating role in promoting urban climate resilience under the CACCP policy. Urban education and public environmental concern have positive moderating effects on the implementation of the CACCP policy, while urban mineral resource dependency has an adverse moderating effect. These findings confirm the effectiveness of climate adaptation policies. It also reveals the financial tools, human capital, cultural values, and economic structural pathways that drive human adaptation to climate change.